Changes in China's wage structure - Suqin Ge; Dennis Tao Yang (Institute for the Study of Labor (IZA), 2012)
Using a national sample of Urban Household Surveys, we document several profound changes in China's wage structure during a period of rapid economic growth. Between 1992 and 2007, the average real wage increased by 202 percent, accompanied by a sharp rise in wage inequality. Decomposition analysis reveals 80 percent of this wage growth to be attributable to higher pay for basic labor, rising returns to human capital, and increases in the state-sector wage premium. Employing an aggregate production function framework, we account for the sources of wage growth and wage inequality in the face of globalization and economic transition. We find capital accumulation, skill-biased technological change, and export expansion to be the major forces behind the evolving wage structure in China.
urn:nbn:de:101:1-2012080812352
Keywords: J31; E24; O40; 330; wage growth; wage premium; capital accumulation; trade expansion; technological change; China